ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN JASA HOTEL SANTIKA PREMIERE SEMARANG - Nandy Dewangga; Wahyu Hidayat; Widiartanto Widiartanto (Universitas Diponegoro, 2014)
The competition of global business today focusing on consumers is a strategic choice in business world in order to survive. For example, the tight competition of business in the company of hotel services is by improving the service quality to consumers. The problems in this research were the decreasing number of hotel service users and the increasing number of consumer complaint as the service users of Santika Premiere Hotel in Semarang from year to year. The aims of this research were to identify the appropriateness level between the expectation and the performance of service implementation including the dimensions of reliability, responsiveness, guarantee, empathy, and direct proof; and to recognize the satisfaction level felt by the guests of Santika Premiere Hotel Semarang. The research type used was the type of Quantitative Descriptive with the number of respondents determined by using Slovin Formula. The number of samples was 100 respondents. The analysis tool used was Importance and Performance Analysis and Cartesius Diagram. The calculation results the score of appropriateness level was 89,22% which means that the performance of the hotel employees was considered appropriate enough by consumers. The satisfaction level was 3,76 which means that consumers feel satisfied enough with the performance of Santika Premiere Hotel Semarang. It is suggested that management Santika Premiere Hotel should repair the facility of laundry by more attention to the cleanliness of washing clothes, performance security officers need to be improved by taking into account the number of hotel guest complaints about the performance of security personnel, the location of mushola is suggested to be near the hotel lobby so that the guests will be easier to worship, Santika Premiere Hotel renovate the design and appearance of the building since the exterior condition of Santika Premiere Hotel was considered quite old compared with the competitors.